EVALUASI PENERAPAN E-PUSKESMAS MENGGUNAKAN MODEL DELONE & MCLEAN DI PUSKESMAS TRUCUK II - Elisabet Christina Endarwati; Ridwan Dwi Irawan; Nibras Faiq Muhammad (STMIK Catur Sakti Kendari, 2026)
Quantitative evaluations of information system success in primary healthcare facilities are still rarely conducted, even though such assessments are important for measuring the system's benefits to users. This study aims to evaluate the implementation of E-Puskesmas at Puskesmas Trucuk II Klaten, which has been operating since January 2023, using the DeLone & McLean model. A quantitative approach was applied using a saturated sampling technique involving 34 respondents. The collected data were analyzed using descriptive statistics and three-stage multiple regression with SPSS. The results showed that all variables fell into the high category (3.61–4.10). Of the nine hypotheses proposed, four were accepted: the effect of system quality on user satisfaction (p = 0.044), the effect of service quality on user satisfaction (p < 0.001; Beta = 0.486) as the strongest influence, the effect of use on user satisfaction (p = 0.013), and the effect of use on net benefits (p = 0.013). The other five hypotheses were rejected. The main obstacles identified included disruptions in BPJS bridging, overly long forms, and manual informed consent. In conclusion, the implementation of E-Puskesmas is considered relatively successful, with service quality being the most dominant factor.